ROLE OF TOTAL QUALITY MANAGEMENT PRACTICES ON PERFORMANCE OF FAIRTRADE PREMIUM PROJECTS IN KENYA - Njung'e, Ruth Muthoni; Kagiri, A. (International Journal of Entrepreneurship and Project Management, 2020)
Purpose: The purpose of this study was to establish the role of total quality management on the performance of fair trade premium projects with particular reference to Flamingo Horticulture Limited (herein referred to as the company or organization). Methodology: The target population for this research comprised of the employees, the management and the fair trade premium committee of the Flamingo Horticulture Limited. The study employed descriptive research design. A census sampling was carried out and the sample size was 46. Survey method was used to solicit the information. The researcher used a questionnaire to collect primary data which was analyzed using qualitative and quantitative analysis techniques then presented in tables. Data collected will be both quantitative and qualitative. Validity and reliability of the questionnaire was enhanced by carrying out a pilot study prior to data collection. The data collected was analyzed using descriptive statistics by aid of Statistical package for social scientists (SPSS). The results were presented in form of Tables. Results: The studies found that quality management planning, customer focus and application of Quality Management planning approaches such as auditing, continuous improvement, monitoring & evaluation have positive effect on performance of fairtrade premium projects. Correlation analysis showed that there were positive and significant correlations between performance of Fairtrade premium projects in Kenya and all independent variables (quality management planning, r=0.537, p<0.05; customer focus, r=0.542, p<0.05; leadership qualities, r=0.476, p<0.05 and, QMS approaches, r=0.452, p<0.05). Unique contribution to theory, practice and policy: The study recommended that Fairtrade organizations should integrate quality management planning in their overall planning process to ensure identification of risks, to ensure that errors are eliminated throughout the operational process and products and services are produced at an optimal quality that can satisfy all stakeholders. Adoption of quality management will enable the leaders to use their personal values, ethics, and commitment to the organization's vision and mission, passionate to energize and create a synergy in teams; heading towards accomplishment of organizational goals. With high level of quality improvement quality management practices and leadership will be higher since leadership qualities are associated with successful quality improvement.